2009
DOI: 10.4103/0028-3886.53277
|View full text |Cite
|
Sign up to set email alerts
|

Chorea as the presentating feature of neurosyphilis

Abstract: Syphilis is still a significant public health problem in developing countries. Although chorea is a very rare manifestation of neurosyphilis, it might be on occasions the initial symptom. This report presents a patients with neurosyphilis who had chorea as the initial presenting symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The clinical manifestations of neurosyphilis are diverse, thus the diagnosis of neurosyphilis should be based on clinical manifestations, TP serological test, and CSF examination, and a single examination is not enough to confirm its diagnosis. [ 10 , 11 ] In this study, serum TRUST test and TPPA test showed positive, CSF leukocyte count and protein concentration increased to different extents, and TPPA and VDRL tests of the CSF showed positive in these patients, which met the diagnostic criteria for neurosyphilis. Moreover, 55% of patients were symptomatic.…”
Section: Discussionsupporting
confidence: 50%
“…The clinical manifestations of neurosyphilis are diverse, thus the diagnosis of neurosyphilis should be based on clinical manifestations, TP serological test, and CSF examination, and a single examination is not enough to confirm its diagnosis. [ 10 , 11 ] In this study, serum TRUST test and TPPA test showed positive, CSF leukocyte count and protein concentration increased to different extents, and TPPA and VDRL tests of the CSF showed positive in these patients, which met the diagnostic criteria for neurosyphilis. Moreover, 55% of patients were symptomatic.…”
Section: Discussionsupporting
confidence: 50%
“…Chorea-ballism may be associated with a variety of factors such as cerebrovascular and inflammatory disease, drugs, metabolic derangement, neurodegenerative disorders, and tumors 15. Hyperglycemia is an unusual cause of chorea-ballism.…”
mentioning
confidence: 99%
“…Cases of influenza A, parvovirus B19 encephalitis, and West Nile virus encephalitis presenting with chorea that slowly improved with supportive care over several weeks [ 15 16 17 ]. When syphilis was the cause, symptoms responded to standard treatment with benzathine penicillin 2.4 million units IM followed by penicillin G 2.4 million units IM for 14 days [ 18 19 ]. In a number of cases, patients were co-infected with syphilis and HIV requiring both antibiotic and antiviral treatments [ 19 20 ].…”
Section: Resultsmentioning
confidence: 99%